(untitled) (Research, Society and Development, 2022)
Objective: To analyze the scientific production of nursing about the daily life of family members in a pediatric oncology unit. Methods: This is an integrative review guided by the PRISMA methodology, using the following databases: LILACS, BDENF, MEDLINE AND PUBMED. The descriptors used were: hospitalized child, family and neoplasms. Sample consisting of: 06 articles. Results: Among the articles analyzed, the largest quantity is aimed at national publication. In relation to the year, 2019 was the one with the highest number of publications. Conclusion: It was evident that family members need to adapt to a new routine in their daily lives during hospitalization, which implies changes in roles and behaviors. The family uses recreational activities and relaxing massages to reduce the stress of daily hospital life. It is worth highlighting the importance of extending care to the family member, in order to expand the care provided to the caregiver as well. Finally, the results of this integrative review brought up the need for more studies focused on everyday life during the hospitalization process of a child undergoing cancer treatment.